Secondhand smoke exposure in toddlerhood and cognitive ability among Malaysian adolescents - Zainol Abidin, Najihah; Zulkifli, Aziemah; Zainal Abidin, Emilia; Abdul Rahman, Anita; Hashim, Zailina; Rasdi, Irniza; Syed Ismail, Sharifah Norkhadijah (Tehran University of Medical Sciences, 2014)
Background: Secondhand Smoke (SHS) exposure has been reported to cause a number of adverse health effects. Although studies have been conducted to identify the link between SHS exposure and cognitive functioning of children, its relationship is still unclear. This study aimed to identify the association of prenatal and postnatal SHS exposure with cognitive ability among adolescents.